Antibacterial activity of Krameria lappacea root extract against gram-positive and gram-negative bacteria and its cytotoxicity on lung and breast cancer cell lines - Abdel-Gaber, Rewaida; Albeshr, Mohammed; Dkhil, Mohamed A.; Almohawis, Nada; Abdelmeguid, Kareem A.; Delic, Denis; Al Quraishy, Saleh; Al-Shaebi, Esam M. (Frontiers in Microbiology, 2025)
IntroductionThe rise of antibiotic-resistant microbes has diminished antibiotic effectiveness, leading to the exploration of alternatives. Krameria lappacea has been used traditionally for various ailments. This study evaluates the in vitro antibacterial and cytotoxic potential of its roots and identifies its active constituents.MethodsRoots of K. lappacea were acquired from a Riyadh market. They were extracted using methanol and the maceration method, followed by phytochemical screening via Liquid Chromatography-Electrospray Ionization-Mass Spectrometry. Antibacterial properties were assessed using agar well diffusion and broth microdilution methods, while cytotoxicity was tested on human lung A549 and MCF7 breast cancer cell lines via MTT assay.ResultsPhytochemical analysis of the extract identified alkaloids, phenolics (including anthraquinones and chlorogenic acids), and flavonoids (such as dihydrokaempferol, epicatechin, and fisetin). The most susceptible bacteria were Staphylococcus aureus and Listeria monocytogenes, both Gram-positive, while Gram-negative Escherichia coli and Salmonella enterica were resistant. Extract effectively suppressed bacterial growth, particularly against L. monocytogenes and S. aureus, showing moderate activity against E. coli and S. enterica, with MBC values higher than MICs. Cytotoxicity testing yielded IC50 values of 142.27 ± 1.02 μg/ml and 64.81 ± 0.26 μg/ml, respectively, compared to doxorubicin.ConclusionOur findings suggest that K. lappacea possesses notable antibacterial activity against Gram-positive bacteria and demonstrates cytotoxic effects against human cancer cell lines, indicating its potential as a natural source of bioactive compounds for antimicrobial and anticancer applications.